Notes From the Field: Secondary Task Precision for Cognitive Load Estimation During Virtual Reality Surgical Simulation Training. (March 2016) - Rasmussen, Sebastian R.; Konge, Lars; Mikkelsen, Peter T.; Sørensen, Mads S.; Andersen, Steven A. W.
Cognitive load (CL) theory suggests that working memory can be overloaded in complex learning tasks such as surgical technical skills training, which can impair learning. Valid and feasible methods for estimating the CL in specific learning contexts are necessary before the efficacy of CL-lowering instructional interventions can be established. This study aims to explore secondary task precision for the estimation of CL in virtual reality (VR) surgical simulation and also investigate the effects of CL-modifying factors such as simulator-integrated tutoring and repeated practice. Twenty-four participants were randomized for visual assistance by a simulator-integrated tutor function during the first 5 of 12 repeated mastoidectomy procedures on a VR temporal bone simulator. Secondary task precision was found to be significantly lower during simulation compared with nonsimulation baseline, p < .001. Contrary to expectations, simulator-integrated tutoring and repeated practice did not have an impact on secondary task precision. This finding suggests that even though considerable changes in CL are reflected in secondary task precision, it lacks sensitivity. In contrast, secondary task reaction time could be more sensitive, but requires substantial postprocessing of data. Therefore, future studies on the effect of CL modifying interventions should weigh the pros and cons of the various secondary task measurements.